1996
DOI: 10.1007/s001050050387
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutische Erfahrungen mit der Extrakorporalen Photopherese Technisches Vorgehen, Überwachung und klinische Ergebnisse bei 41 Hautkranken

Abstract: Extracorporeal photophoresis (ECP), a therapeutic modality that has been under investigation for some years, is based on separation of a leucocyte/lymphocyte-enriched cell fraction from the peripheral blood, extracorporeal treatment of the cells with 8-MOP/UVA and subsequent reinfusion of the cells in the patient. Its main effects seem to consist in changes to the immunologic behaviour of the photoinactivated/modulated cells. The immune response of the host is obviously stimulated by this treatment. ECP is nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…ECP has been shown to cause clinical improvement and prolonged survival in patients with erythrodermic cutaneous T-cell lymphoma in the absence of limiting side effects [1, 2, 3, 4, 5]. This finding is remarkable since it has been shown that overall survival of patients with cutaneous T-cell lymphoma was not altered by conventional X-ray treatment or chemotherapy [5, 8].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…ECP has been shown to cause clinical improvement and prolonged survival in patients with erythrodermic cutaneous T-cell lymphoma in the absence of limiting side effects [1, 2, 3, 4, 5]. This finding is remarkable since it has been shown that overall survival of patients with cutaneous T-cell lymphoma was not altered by conventional X-ray treatment or chemotherapy [5, 8].…”
Section: Discussionmentioning
confidence: 48%
“…Regimens combining ECP with interferon α (IFN-α), psoralen photochemotherapy and/or radiation were also successful in patients with tumor stage cutaneous T-cell lymphoma and lymph node involvement [4]. In addition to the clinical improvement a long-term, disease-free remission could be induced by ECP in a minority of patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…The entire ECP procedure performed in this study has been described in detail elsewhere [18]. ECP was carried out at 4-week intervals in 2 sessions on 2 successive days (corresponding to one ECP cycle).…”
Section: Methodsmentioning
confidence: 99%
“…Eine modifizierte Eigenbluttherapie wurde in den 90er Jahren mit thrombozyta Èren Wachstumsfaktoren (PDWHF, plateled-derived wound healing factor) in der bioregulativen Wundheilungstherapie eingesetzt [10]. Zu den weiteren modernen Eigenbluttherapien geho È rt die extrakorporale Photophorese (ECP), die wahrscheinlich eine Modifikation der T-Zell-Rezeptoren bewirkt [11].…”
Section: Beispiel: Ausleitende Verfahrenunclassified